pH Control Enables Simultaneous Enhancement of Nitrogen Retention and N2O Reduction in Shewanella loihica Strain PV-4 - Kim, Hayeon; Park, Doyoung; Yoon, Sukhwan (Frontiers in Microbiology, 2017)
pH has been recognized as one of the key environmental parameters with significant impacts on the nitrogen cycle in the environment. In this study, the effects of pH on NO3-/NO2- fate and N2O emission were examined with Shewanella loihica strain PV-4, an organism with complete denitrification and respiratory ammonification pathways. Strain PV-4 was incubated at varying pH with lactate as the electron donor and NO3-/NO2- and N2O as the electron acceptors. When incubated with NO3- and N2O at pH 6.0, transient accumulation of N2O was observed and no significant NH4+ production was observed. At pH 7.0 and 8.0, strain PV-4 served as a N2O sink, as N2O concentration decreased consistently without accumulation. Respiratory ammonification was upregulated in the experiments performed at these higher pH values. When NO2- was used in place of NO3-, neither growth nor NO2- reduction was observed at pH 6.0. NH4+ was the exclusive product from NO2- reduction at both pH 7.0 and 8.0 and neither production nor consumption of N2O was observed, suggesting that NO2- regulation superseded pH effects on the nitrogen-oxide dissimilation reactions. When NO3- was the electron acceptor, nirK transcription was significantly upregulated upon cultivation at pH 6.0, while nrfA transcription was significantly upregulated at pH 8.0. The highest level of nosZ transcription was observed at pH 6.0 and the lowest at pH 8.0. With NO2- as the electron acceptor, transcription profiles of nirK, nrfA, and nosZ were statistically indistinguishable between pH 7.0 and 8.0. The transcriptions of nirK and nosZ were severely downregulated regardless of pH. These observations suggested that the kinetic imbalance between N2O production and consumption, but neither decrease in expression nor activity of NosZ, was the major cause of N2O accumulation at pH 6.0. The findings also suggest that simultaneous enhancement of nitrogen retention and N2O emission reduction may be feasible through pH modulation, but only in environments where C:N or NO2-:NO3- ratio does not exhibit overarching control over the NO3-/NO2- reduction pathways.